2011
DOI: 10.1098/rstb.2010.0414
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to placebo effects in medicine: mechanisms and clinical implications

Abstract: The field of placebo research has made considerable progress in the last years and it has become a major focus of interest. We know now that the placebo effect is a real neurobiological phenomenon and that the brain's 'inner pharmacy' is a critical determinant for the occurrence of psychobiological and behavioural changes relevant to healing processes and well-being. However, harnessing the advantages of placebo effects in healthcare is still a challenge. The first part of the theme issue summarizes and discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 61 publications
0
45
0
2
Order By: Relevance
“…Additionally, placebo administration for analgesia has been shown to act on the endogenous opioid system, with its effects reversed by the opioid antagonist naloxone [29]. In Parkinson’s disease, the placebo response has been linked to dopamine release in the striatum and neuronal activity in the subthalamic nucleus, both of which are key brain regions affected by Parkinson’s disease and are associated with motor control [3032]. Research on the conditioned immune response has demonstrated involvement of the insular cortex, amygdala, and ventromedial nucleus of the hypothalamus [33].…”
Section: What Are the Mechanisms Behind The Placebo Effect?mentioning
confidence: 99%
“…Additionally, placebo administration for analgesia has been shown to act on the endogenous opioid system, with its effects reversed by the opioid antagonist naloxone [29]. In Parkinson’s disease, the placebo response has been linked to dopamine release in the striatum and neuronal activity in the subthalamic nucleus, both of which are key brain regions affected by Parkinson’s disease and are associated with motor control [3032]. Research on the conditioned immune response has demonstrated involvement of the insular cortex, amygdala, and ventromedial nucleus of the hypothalamus [33].…”
Section: What Are the Mechanisms Behind The Placebo Effect?mentioning
confidence: 99%
“…We have also seen that simple equations such as anger leading to stomach ulcers, anxiety to asthma, repressed hostility to myocardial infarction, are nearly always wrong in their linear simplicity. However, the generic possibilities of such connections have been unraveled, based on the discovery that the whole body and not only the Central-Nervous-System (CNS) is a complex network communication system and continues to be researched [108]. It can be expected that in the near future, this research program will generate a more specific and detailed understanding of how some somatic diseases are linked to psychological states.…”
Section: Psychosomatic Medicine Psycho-neuro-endocrinology and Psychmentioning
confidence: 99%
“…Many other studies have highlighted placebo effects targeting autonomic functions of the respiratory, gastrointestinal and cardiovascular systems [63].…”
Section: Placebo Responses Can Employ Brain -Body Pathwaysmentioning
confidence: 99%